ANALISA TRANSFER PANAS PADA KONDENSASI LUAR DENGAN MENGGUNAKAN REFRIGERANT R-134a - Hadi Rahmad; Zulfa Khalida; Saiful Arif (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
An experimental study in condensation has been conducted to analyse the condensation phenomena. The enhancement heat transfer performance is as always highlighted phenomenon for being investigated. The modified surface is a common method for enhancing the performance of condensation since inducing the droplet on the surface. The droplet leads to increasing heat-transfer area, decreasing thermal resistance, and shorten the condensing cycle. The condensation by using water successfully induces droplets on the surface and enhances the heat transfer. But water and refrigerant have different fluid properties which induce different phenomena whereas refrigerant is widely used in industry. In this case, the condensation is conducted on the modified surface by using a commercial promotor to investigate the phenomena. The investigation results show that the surface tension immensely influences the condensate on the surface. Refrigerant is low surface tension fluid which leads to the difficulty of fluid for inducing droplets and almost no enhancement heat transfer performance since the results almost fitted well to Nusselt bare tube prediction around 2443-3063 W/m2 oC with subcooled temperature 2 up to 5 oC.